Effects of supplemental levels of zinc, copper, and manganese on apparent absorption and tissue retention in growing bulls - J.-B. Daniel; J. Martín-Tereso (Journal of Dairy Science, 2025)
ABSTRACT: Apparent trace metal absorption and tissue retention upon incremental levels of supplemental Zn, Cu, and Mn were studied in growing cattle. A total of 60 Holstein bulls (age = 246 ± 5 d, BW = 329 ± 26 kg) were enrolled for the study and fed for 6 to 9 wk a diet (78, 15, and 91 mg/kg DM for Zn, Cu, and Mn, respectively) consisting of barley straw (15%), molasses (10%), and a pelleted concentrate (75%). Thereafter, 20 bulls were randomly selected and slaughtered for determination of a baseline tissue trace metal composition. The remaining 40 bulls (age = 293 ± 9 d, BW = 385 ± 21 kg) were then blocked based on BW in 8 blocks of 5 bulls. Bulls within a block were randomly assigned to 1 of 5 diets defined by increasing supplemental levels of Zn, Cu, and Mn (all in the sulfate salt form), with the following total dietary contents, respectively: basal diet with no supplementation of Zn, Cu, Mn; 38, 7, and 47 mg/kg DM), with supplementation of 20 mg Zn/kg DM, 5 mg Cu/kg DM, and 20 mg Mn/kg DM (61, 11, and 68 mg/kg DM), with supplementation of 40 mg Zn/kg DM, 10 mg Cu/kg DM, and 40 mg Mn/kg DM (78, 15, and 91 mg/kg DM), with supplementation of 80 mg Zn/kg DM, 20 mg Cu/kg DM, and 80 mg Mn/kg DM (123, 26, and 136 mg/kg DM), or with supplementation of 160 mg Zn/kg DM, 40 mg Cu/kg DM, and 160 mg Mn/kg DM (195, 43, and 214 mg/kg DM). These diets were fed for 12 wk, and a complete collection of feces and urine was performed on wk 4, 8, and 12 to determine trace metal balance (intake − feces − urine) and apparent absorption. After this feeding period, all bulls were slaughtered and gastrointestinal tissues, whole organs (heart, liver, spleen, and kidney), bile, cervical vertebra, and tibia were collected at the slaughterhouse. All samples were dried, ground, and analyzed for trace metals. Linear and quadratic effects of dietary trace metal supplementation were evaluated using a model that included block as a fixed effect and week as a repeated measure when applicable. Increasing supplemental levels of Zn, Mn, and Cu resulted in linear increases in fecal output of all 3 metals, with 90%, 89%, and 98% of the additional Zn, Mn, and Cu fed being lost in feces. Apparent Mn and Cu absorption efficiency decreased quadratically with increasing supplementation rate, whereas apparent Zn absorption efficiency was not significantly affected, resulting in a linear increase in Zn balance. Despite a decreasing absorption efficiency, Mn balance also linearly increased with supplementation rate, whereas Cu balance was not significantly affected. Hepatic Cu increased with higher Cu intakes, but the marginal rate of increase diminished as Cu intake increased. For all gut tissues, Mn concentration increased linearly with Mn intake. Remarkably, urinary Zn, Mn, and Cu excretions were all linearly increased with greater dietary intakes. Although the total amounts of urinary excretions were low (<0.3% of intake), these results suggest increasing metabolic availability at higher trace metal intake. This may suggest that the primary regulatory mechanisms of trace metal homeostasis were overwhelmed, even at feeding levels that are commonly encountered in practical settings.